Strategy for economic development of backward regions - Singh, Abhimanyu, 1940- (New Delhi : Anmol Publications, 1997)
Study with reference to Bihar, India.
Includes bibliographical references and index.
Keywords: Bihar (India) -- Economic conditions; Bihar (India) -- Rural conditions